Optimization of Factors Affecting Acid Hydrolysis of Water Hyacinth Stem (Eichhornia Crassipes) for Bio-Hydrogen Production. (November 2015) - Pattra, Sakchai; Sittijunda, Sureewan
Abstract: Response surface methodology (RSM) with central composite design (CCD) was applied to optimize hydrolysis conditions of water-hyacinth stem (WHS). Firstly, the effects of reaction time (h), % diluted H2 SO4 concentration (v/v) and shaking speed (rpm) for hydrolyze WHS were investigated. The optimum condition for WHS hydrolysis was reaction time of 7.73 h, H2 SO4 concentration of 1.31% (v/v) and stirring speed of 264.41 rpm in which a maximum total sugar of 13 g/L was obtained. Secondly, the hydrolysate WHS obtained from the optimum hydrolysis condition was further used as the substrate for hydrogen production by heat-treated anaerobic sludge. Results showed that the maximum HP of 127. 6 mmol H2 /L was obtained.